2008
DOI: 10.1248/cpb.56.1362
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Dispyrin, Purpurealidin E, and Aplysamine-1

Abstract: Bromotyrosine alkaloids dispyrin (1), purpurealidin E (2), and aplysamine-1 (3) isolated from marine sponge, were synthesized from commercially available tyramine (4) as a common starting material. The overall yield was 18%, 39%, and 22% for 1 from 4 in 5 steps, 2 in 5 steps, and 3 in 6 steps, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Synthesis of the simplified purpurealidin analogs was based on the amide coupling of purpurealidin E 4 or tyramine derivative 11 with aromatic carboxylic acids. Purpurealidin E 4 and 11 were synthesized in four steps from tyramine in an overall yield of 80% and 82%, respectively, improving the literature yields ( Fig 2 ) [ 4 , 13 , 14 ]. The synthetic route started with the bromination of tyramine.…”
Section: Resultsmentioning
confidence: 88%
“…Synthesis of the simplified purpurealidin analogs was based on the amide coupling of purpurealidin E 4 or tyramine derivative 11 with aromatic carboxylic acids. Purpurealidin E 4 and 11 were synthesized in four steps from tyramine in an overall yield of 80% and 82%, respectively, improving the literature yields ( Fig 2 ) [ 4 , 13 , 14 ]. The synthetic route started with the bromination of tyramine.…”
Section: Resultsmentioning
confidence: 88%
“…395 Dispyrin (Agelas dispar) 459 and purpurealidin (Psammaplysilla purpurea) 460 were synthesised from tyramine. 461 In a separate synthetic study, dispyrin was found to be a potent ligand and antagonist of a 1D and a 2A adrenergic and H2 and H3 histamine receptors. 462 Aplysamine 6 440, obtained from a Pseudoceratina sp.…”
Section: Green Algaementioning
confidence: 97%
“…Introduction of a bromine atom at 5 was carried out by reported method in 2 steps. 15) Di-brominated phenol (6) was treated with iodide (8), which was prepared from N-(3-hydroxyproyl)phthalimide (7), 18) in the presence of potassium carbonate (K 2 CO 3 ) and benzyltriethylammonium chloride (BTAC) provided ether (9) in high yields (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
“…IR spectra were recorded on a JASCO FT/IR-6300 spectrophotometer; ATRϭattenuated total reflectance system. NMR spectra were recorded on a JEOL JNM-ECX400 ( 15,18) Synthesis of Ether (9) A mixture of phenol (6) (410 mg, 1.04 mmol), iodide (8) (325 mg, 1.03 mmol), BTAC (24 mg, 0.105 mmol), and K 2 CO 3 (290 mg, 2.10 mmol) in CH 3 CN (6.0 ml) was stirred at rt for 48 h. The reaction mixture was poured into water, and extracted with AcOEt. The organic layer was washed with water and brine, dried over Na 2 SO 4 , and evaporated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation